Defect or Defend : Military Responses to Popular Protests in Authoritarian Asia - Lee, Terence, 1972- (Book collections on Project MUSE., 2015)
This book will appeal to students and scholars of comparative politics, Asian studies, security studies, and international relations, as well as defense policymakers.